Chemotherapy followed by modified donor lymphocyte infusion as a treatment for relapsed acute leukemia after haploidentical hematopoietic stem cell transplantation without in vitro T‐cell depletion: superior outcomes compared with chemotherapy alone and an analysis of prognostic factors. (17th August 2013) - Yan, Chen‐Hua; Wang, Jing‐Zhi; Liu, Dai‐Hong; Xu, Lan‐Ping; Chen, Huan; Liu, Kai‐Yan; Huang, Xiao‐Jun
Abstract: We retrospectively compared the antileukemic effects of chemotherapy alone and chemotherapy followed by modified donor lymphocyte infusion (DLI) in 82 patients with relapsed acute leukemia after haploidentical hematopoietic stem cell transplantation (HSCT) without in vitro T‐cell depletion. We also investigated prognostic factors in patients receiving chemotherapy followed by modified DLI. Thirty‐two patients received chemotherapy alone, and the remaining 50 patients received chemotherapy followed by modified DLI. In patients receiving chemotherapy followed by modified DLI, complete remission rate was significantly higher (64.0% vs. 12.5%, P =  0.000), the incidence of relapse was significantly lower (50.0% vs. 100.0%, P  =   0.000), and disease‐free survival was significantly improved (36.0% vs. 0.0%, P =  0.000) compared with patients receiving chemotherapy alone. Multivariate analysis demonstrated that patients with chronic graft‐versus‐host disease (GVHD) after intervention ( P =  0.000) and patients receiving chemotherapy followed by modified DLI ( P =  0.037) were associated with a lower relapse rate. Furthermore, in patients receiving chemotherapy followed by modified DLI, multivariate analysis demonstrated that chronic GVHD after modified DLI ( P =  0.039) and duration of minimal residual disease (MRD) (−) ≥4 months after modified DLI ( P =  0.001) were associated with a lower relapse rate. Our study is the first to suggest that chemotherapy followed by modified DLI is associated with stronger antileukemic effects and better survival in relapsed acute leukemia after haploidentical HSCT without in vitro T‐cell depletion. Furthermore, our study suggests that lack of chronic GVHD and duration of MRD (−) <4 months after modified DLI are associated with higher relapse rates in patients receiving chemotherapy followed by modified DLI.